2017
DOI: 10.1017/jmo.2017.54
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging leader–leader exchange to enrich the effect of leader–member exchange on team innovation

Abstract: AbstractIn this study, I propose supervisors’ upward leader–leader exchange relationships as an important boundary condition for the relationship between average leader–member exchange (LMX) relationships and a climate for innovation support at the group level. Specifically, I argue that the effect of resource spillover to poor-LMX subordinates within a work group is an important mechanism that leads to the development of a climate that supports innovation. I test the hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Given the barriers to employee creativity, it is clear that the leader is an important actor in creating a positive organizational climate and overcoming obstacles (Hon et al, 2013). The supportive attitudes and behaviors exhibited by the leaders play a critical role in solving the problems experienced by the employees during the creative process and in creating the climate required for creativity (Yang, 2020). Supporting the literature, Crossan and Apaydin (2010) examined the studies on creativity and innovation conducted in the last 27 years and emphasized the importance of leadership as one of the three main determinants of creativity (business processes, managerial levers, and leadership).…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Given the barriers to employee creativity, it is clear that the leader is an important actor in creating a positive organizational climate and overcoming obstacles (Hon et al, 2013). The supportive attitudes and behaviors exhibited by the leaders play a critical role in solving the problems experienced by the employees during the creative process and in creating the climate required for creativity (Yang, 2020). Supporting the literature, Crossan and Apaydin (2010) examined the studies on creativity and innovation conducted in the last 27 years and emphasized the importance of leadership as one of the three main determinants of creativity (business processes, managerial levers, and leadership).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The positive attitude of the authentic leader toward different opinions and suggestions among the employees, and the tendency to create a more constructive atmosphere instead of applying punishment in case of mistakes create a positive organizational climate for employee creativity (Toor & Ofori, 2008). In such a positive organizational climate, employees do not hesitate to display creative behavior by manifesting their creative personalities (Yang, 2020). Research has indicated that a supportive organizational climate is indispensable for employees to display creative behaviors (Akgunduz, Alkan, & Gök, 2018).…”
Section: Authentic Leadership and Employee Creativitymentioning
confidence: 99%
See 3 more Smart Citations